2019
DOI: 10.7759/cureus.5983
|View full text |Cite
|
Sign up to set email alerts
|

Cavitary Pulmonary Infarction in a Case of Pulmonary Embolism After Successful Vascular Recanalization

Abstract: Cavity formation after pulmonary embolism can be a result of infarction; however, the data available on the incidence rate were obtained from the cases of patients treated with anticoagulation without recanalization. It is yet unknown if interventions like catheter-directed alteplase or thrombectomy reduce the risk of cavity formation. We present an interesting case of a patient who developed pulmonary cavity and possible secondary infection after successful vascular recanalization with catheter-directed altep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…5 Previous studies have suggested prompt surgery owing to a 73% mortality rate in medical treatment of infected pulmonary cavitation, which is theorized to be due to an insufficient blood supply and a risk of persistent infection. 4 Successful experiences of some separate cases of infected cavitating pulmonary infarction have been reported, 3,4,10 but no recent series have mentioned the prognosis of infected pulmonary cavitation followed by acute PE. Studies published in the past decades have consistently shown a progressive reduction in the fatality rate in patients with acute PE.…”
Section: Discussionmentioning
confidence: 99%
“…5 Previous studies have suggested prompt surgery owing to a 73% mortality rate in medical treatment of infected pulmonary cavitation, which is theorized to be due to an insufficient blood supply and a risk of persistent infection. 4 Successful experiences of some separate cases of infected cavitating pulmonary infarction have been reported, 3,4,10 but no recent series have mentioned the prognosis of infected pulmonary cavitation followed by acute PE. Studies published in the past decades have consistently shown a progressive reduction in the fatality rate in patients with acute PE.…”
Section: Discussionmentioning
confidence: 99%